DO LEADERSHIP QUALITIES DETERMINE COMPETENT PRINCIPALS - Sharma, Sailesh (Innovare Journal of Education, 2015)
There has been limited research on how leadership potential is influenced by leadership quality of school principals. The purpose of this quantitative study is to present some of the findings derived from the study of teachers' perception on leadership qualities and leadership competencies of their principals. This study utilized questionnaire titledÂ Â â€˜Leadership attributes of my principal' developed by Sharma (2010). This questionnaire comprises of two variables â€“ leadership qualities and leadership competencies of principals. Leadership qualities have eight dimensions while competencies have five. The questionnaire was administered on 154 teachers from reputed private schools in India. The data obtained was subjected to analysis of descriptive statistics, correlation and multiple regressions. The findings indicated that principals were rated to be excellent in leadership qualities and competencies by their teachers. Furthermore all the eight dimensions of leadership qualities are proved to be significant determinant for leadership competencies Key Words : School Principals, Leadership, Leadership Qualities, Leadership Competencies